Ku duszpasterstwu Kościoła domowego - Pacholak, Paweł (Studia Pastoralne, 2009)
We are making an attempt to outline the foundations of the ministryministry of marriages and families, which lead to the formulation of our basic thesis, expressed in the title: „Toward the ministry of the domestic Church”. There is no intention of this study to postulate changes concerning names or transformation of existing structures. Its essential aim, is to point out the practical dimension of marriage and family as a domestic Church, functioning in the teaching of the Church and in the theory of the ministry of the family. The idea of the domestic church, deeply rooted in Church tradition, contains very vaulable intuitions for a pastoral vision of the ministry of marriages and families. The analysis of the concept brings to mind the authentically ecclesiastic character of a Christian marriage and a family growing out of the marriage. This analysis points at principled spheres of activity in aid of marriages and families, what was first done by John Paul II. The Pope, by continuing the thought of the Second Vatican Council and of Pope Paul VI, emphasized the role of bringing up children, evangelical missionary tasks of families and the dimension of families’ engaging in ministry as a sign of the ecclesiastic character of Christian marriage and family. These observations lead to the specification of postulates of ministry, which aim at the authentic discovery of a family as a domestic Church. What seems to be the most important in preparation for marriage is faith formation of an engaged couple, who start building a marriage and a family community. Next of analysed spheres is sacramental life of members of a Christian family and the interpretation of the reality of a domestic Church as a space of the administration of the sacraments. And finally, this analysis closes with an attempt to verify universal ministry actions, while building a domestic Church and pro-family sensitivity among people who still live in different kinds of family relations.